2017
DOI: 10.3390/d9010015
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Endogenous and Exogenous Nutrition on Larval Development for Crown-Of-Thorns Starfish

Abstract: Abstract:Outbreaks of crown-of-thorns starfish are often attributed to step-changes in larval survivorship following anomalous increases in nutrients and food availability. However, larval growth and development is also influenced by the nutritional condition of spawning females, such that maternal provisioning may offset limitations imposed by limited access to exogenous sources of nutrients during the formative stages of larval development. This study examined the individual, additive, and interactive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 57 publications
(102 reference statements)
0
21
2
Order By: Relevance
“…Laboratory experiments by Wolfe et al (2015aWolfe et al ( , 2017 demonstrated high larval survival and settlement success across a broad range of nutrient levels, and most importantly, below the lower threshold levels previously suggested by Fabricius et al (2010). The robust nature of larvae, even in oligotrophic conditions, may be driven by increased investment in provisioning of eggs by well-fed adults ) and the morphological plasticity of larvae to respond to changes in the availability of exogenous prey (Wolfe et al 2015b;Caballes et al 2017a). …”
Section: Questions 1 and 3 (Larvae And Juveniles) -Are High Nutrient Comentioning
confidence: 88%
See 4 more Smart Citations
“…Laboratory experiments by Wolfe et al (2015aWolfe et al ( , 2017 demonstrated high larval survival and settlement success across a broad range of nutrient levels, and most importantly, below the lower threshold levels previously suggested by Fabricius et al (2010). The robust nature of larvae, even in oligotrophic conditions, may be driven by increased investment in provisioning of eggs by well-fed adults ) and the morphological plasticity of larvae to respond to changes in the availability of exogenous prey (Wolfe et al 2015b;Caballes et al 2017a). …”
Section: Questions 1 and 3 (Larvae And Juveniles) -Are High Nutrient Comentioning
confidence: 88%
“…solaris, based on contrasting diets (e.g., Acropora versus Porites), have a major bearing on the growth and performance of their progeny. Well-fed females provision their offspring with increased levels of endogenous energetic reserves, which not only allows larvae to withstand prolonged periods of starvation, but also enables them to grow larger and feed more efficiently (Wolfe et al 2015b;Caballes et al 2017a). Larval survivorship in the wild will also be limited by competition, predation and environmental constraints on development (see sections 2.13 and 2.14).…”
Section: Question 4 (Larvae and Juveniles) -How Important Is Diet In mentioning
confidence: 99%
See 3 more Smart Citations